Street-Level View of Community Policing in the United States, 1995 - Langston, Elizabeth ([Verlag nicht ermittelbar], 2000)
This study sought to examine community policing from a street-level officer's point of view. Active community police officers and sheriff's deputies from law enforcement agencies were interviewed about their opinions, experiences with, and attitudes toward community policing. For the study 90 rank-and-file community policing officers from 30 law enforcement agencies throughout the United States were selected to participate in a 40- to 60-minute telephone interview. The survey was comprised of six sections, providing information on: (1) demographics, including the race, gender, age, job title, highest level of education, and union membership of each respondent, (2) a description of the community policing program and daily tasks, with questions regarding the size of the neighborhood in terms of geography and population, work with citizens and community leaders, patrol methods, activities with youth/juveniles, traditional police duties, and agency and supervisor support of community policing, (3) interaction between community policing and non-community policing officers, (4) hours, safety, and job satisfaction, (5) police training, and (6) perceived effectiveness of community policing.